Implementation of QbD for development of a downstream process for a therapeutic biosimilar - Rathore, Anurag; Bhambure, Rahul (253rd National Meeting of the American-Chemical-Society (ACS) on Advanced Materials, Technologies, Systems, and Processes, 2017)

Engineering staphylococcal protein A for high-throughput affinity purification of monoclonal antibodies - Amritkar, Vinod; Adat, Satish; Tejwani, Vijay; Rathore, Anurag; Bhambure, Rahul (Biotechnology Advances, 2020)
Protein A chromatography is one of the most widely used purification steps in the manufacturing of the various classes of recombinant and non-recombinant antibodies. Due to the higher cost, lower binding capacity, and limited life cycle of Protein A ligand, this affinity-based purification step is often one of the most significant contributors to the cost of manufacturing of monoclonal antibody (mAb) products. In the last decade, there has been significant progress in improving the Protein A chromatography throughput by designing new engineered Staphylococcal Protein A (SPA) variants with higher dynamic binding capacity, considerable alkaline tolerance, and mild acidic elution pH. This review aims at summarizing the various protein engineering approaches used for improving the throughput of the Protein A-based affinity purification of various immunoglobulins. With biopharmaceutical producers operating under ever-increasing pressure towards reducing the cost of manufacturing, these advances in engineered protein A variants will help in processing larger cell culture volumes with high throughput and thereby significantly lower the cost of raw materials.
Keywords: Alkaline tolerance; Dynamic binding capacity; Elution pH; Monoclonal antibodies; Protein A

Dimerization of SARS-CoV-2 nucleocapsid protein affects sensitivity of ELISA based diagnostics of COVID-19 - Khan, Wajihul; Khan, Nida; Mishra, Avinash; Gupta, Surbhi; Bansode, Vikrant; Mehta, Deepa; Bhambure, Rahul; Rathore, Anurag (International Journal of Biological Macromolecules, 2022)
Nucleocapsid protein (N protein) is the primary antigen of the virus for development of sensitive diagnostic assays of COVID-19. In this paper, we demonstrate the significant impact of dimerization of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) N-protein on sensitivity of enzyme-linked immunosorbent assay (ELISA) based diagnostics. The expressed purified protein from E. coli is composed of dimeric and monomeric forms, which have been further characterized using biophysical and immunological techniques. Indirect ELISA indicated elevated susceptibility of the dimeric form of the nucleocapsid protein for identification of protein-specific monoclonal antibody as compared to the monomeric form. This finding also confirmed with the modelled structure of monomeric and dimeric nucleocapsid protein via HHPred software and its solvent accessible surface area, which indicates higher stability and antigenicity of the dimeric type as compared to the monomeric form. The sensitivity and specificity of the ELISA at 95% CI are 99.0% (94.5-99.9) and 95.0% (83.0-99.4), respectively, for the highest purified dimeric form of the N protein. As a result, using the highest purified dimeric form will improve the sensitivity of the current nucleocapsid-dependent ELISA for COVID-19 diagnosis, and manufacturers should monitor and maintain the monomer-dimer composition for accurate and robust diagnostics.